Analisis Kekerasan Simbolik dalam Cerpen Viyon no Tsuma Karya Dazai Osamu - Mulyaningrum, Meilia; Firmansyah, Dian Bayu; Haryono, Haryono (Universitas Negeri Semarang, 2020)
This study aims to described the symbolic violence done by Otani and its mechanism on Dazai Osamu’s short story, Viyon No Tsuma. Close reading and note taking method was conducted to collect the data. Collected data such as form of words, sentences, sentence fragments, paragraph, and paragraph fragments, were grouped in a table form and analyzed using analytic descriptive method. Data analysis results showed that (1) Otani’s habits are calm, even when he was drunk, and dress neatly. However, by the time flies, Otani changes to be rude and irresponsible man; (2) the fields existed in the short story are economic field and social field; (3) the highest capital is owned by Otani, it is a symbolic capital in the form of the nobility of Otani’s family; (4) All of symbolic violences are done by mechanism of eufemisation.